AN ANALYSIS OF METAPHOR IN PEOPLE MAGAZINE’S ADVERTISEMENTS - Fenty Triartha; Siti Aisah Gintin (State University of Medan, 2012)
ABSTRACT The objectives of this research were to find out the five concepts of lexical metaphor, namely: Noun-noun, noun-verb, noun-adjective, sound concepts, social concepts and the dominant one used in People Magazine’s advertisements. This research was conducted by using qualitative descriptive design. It took fifty advertisements taken randomly from People magazines which were published in March 2011 until December 2011. The result of analyzing found five concepts of lexical metaphor were used in the advertisements in People Magazine, they were: noun-noun, noun-verb, noun-adjective, sound concepts and social concepts.